2000
DOI: 10.1073/pnas.150243397
|View full text |Cite
|
Sign up to set email alerts
|

Subnucleus-specific loss of neurons in medial thalamus of schizophrenics

Abstract: The hypoactivity of dorsolateral prefrontal cortex in schizophrenics is well known. One cause of this hypoactivity may be defective corticocortical or thalamocortical connections. Recent imaging studies of the thalamus suggest reductions in volume of the whole thalamus and reduced activity in the medial group of thalamic nuclei, which may indicate loss of functional input to the cortex. Using stereological techniques in six pairs of individually matched brains from schizophrenics and controls, we measured the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 50 publications
8
162
3
Order By: Relevance
“…A number of studies indicate that heteromodal areas of the association cortex, including the prefrontal cortex, are key sites of pathology in the schizophrenic brain (Pearlson et al, 1996;Barch et al, 2001;Selemon, 2001). Thalamic nuclei that are reciprocally connected with heteromodal cortical areas have been shown to be smaller and have fewer neurons in schizophrenic subjects (Pakkenberg, 1990;Popken et al, 2000;Young et al, 2000;Byne et al, 2002;Danos et al, 2002;; however, our analysis suggests that the LGN does not exhibit comparable reductions in volume and neuronal number.…”
Section: Clinical Context Of Visual Deficits In Schizophreniamentioning
confidence: 52%
See 2 more Smart Citations
“…A number of studies indicate that heteromodal areas of the association cortex, including the prefrontal cortex, are key sites of pathology in the schizophrenic brain (Pearlson et al, 1996;Barch et al, 2001;Selemon, 2001). Thalamic nuclei that are reciprocally connected with heteromodal cortical areas have been shown to be smaller and have fewer neurons in schizophrenic subjects (Pakkenberg, 1990;Popken et al, 2000;Young et al, 2000;Byne et al, 2002;Danos et al, 2002;; however, our analysis suggests that the LGN does not exhibit comparable reductions in volume and neuronal number.…”
Section: Clinical Context Of Visual Deficits In Schizophreniamentioning
confidence: 52%
“…As reduction of thalamic volume and neuronal number has been described in several association nuclei of the thalamus, including the mediodorsal, anterior, pulvinar, and ventral lateral posterior nuclei (Pakkenberg, 1990;Popken et al, 2000;Young et al, 2000;Byne et al, 2002;Danos et al, 2002;, one possible explanation for the absence of cell loss in the LGN is that neuronal pathology in schizophrenia is restricted to nuclei with reciprocal connections to higher association cortices. It should be noted, however, that none of the postmortem studies that have described neuronal deficits in schizophrenic patients examined brains from the Stanley Foundation, the cohort that was analyzed in the present study.…”
Section: Comparable Cell Number In Schizophrenic and Control Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inference can be strengthened by comparing related measures between postmortem and in vivo imaging studies. For example, the likelihood that the reductions in volume and neuron number observed in the postmortem mediodorsal thalamus of subjects with schizophrenia (Pakkenberg 1990;Popken et al 2000;Young et al 2000) are related to the primary disease process is supported by the reported reductions in total thalamic volume (Buchsbaum et al 1996;Gur et al 1998;Gilbert et al 2001) and in the size of the mediodorsal nucleus (Byne et al 2001) in first-onset, never-medicated subjects with schizophrenia. A third strategy that has been less frequently utilized is the study of unaffected relatives of ill subjects.…”
Section: Well-controlled Confoundsmentioning
confidence: 99%
“…For example, three published studies have found evidence of reduced numbers of glial cells in regions of the frontal cortex in subjects with depression (Ongur et al 1998;Rajkowska et al 1999;Cotter et al 2001). Within the field of schizophrenia research, three published studies have reported a similar ‫ف‬ 30% decrement in the number of neurons in the mediodorsal thalamic nucleus (Pakkenberg 1990;Popken et al 2000;Young et al 2000), two groups have found a reduction of somal size in deep layer 3 pyramidal neurons in prefrontal area 9 (Rajkowska et al 1998;Pierri et al 2001) and three independent research groups have found decreased expression of the mRNA for the 67 kilodalton isoform of glutamic acid decarboxylase (GAD 67 ), the synthesizing enzyme for GABA, in the dorsal prefrontal cortex (Akbarian et al 1995; Guidotti et al 2000;Volk et al 2000) of subjects with schizophrenia.Consequently, the opportunity for studies of the postmortem human brain to exploit rapidly developing technologies in the service of advancing our knowledge of psychiatric disorders has never been greater. However, as in any area of scientific investigation, such studies must be conducted with an adequate awareness of their strengths and limitations, and with appropriate attention to the types of issues that can maximize the strengths and mitigate the limitations.…”
mentioning
confidence: 99%